Pengaruh Model Pembelajaran Investigasi Kelompok Terhadap Minat Belajar Siswa pada Materi Sistem Persamaan Linier Dua Variabel di Kelas VIII - Rafikha Turahmi; Siti Khayroiyah (Prodi Pendidikan matematika Universitas Islam Majapahit (UNIM), Mojokerto, Indonesia, 2022)
This study aims to see the effect of the group investigation learning model on students' learning interest in the material of a two-variable linear equation system in class VIII of SMPN 2 Kabun. This research is a quantitative research, using simple regression analysis and correlation. The sample in this study wes all students of class VIII-A SMPN 2 Kabun, totaling 31 students. The instrument used by the researcher was to raise student interest in learning. The results of this study indicate that the regression equation ? = 23,773 + 0,879X and the results of the regression line Freg = 47,879. When compared with Ftable at a significant level of 5% = 4.17, then Freg > Ftable. As a result, there is an effect of the group investigation learning model on students' learning interest in the material of a two-variable system of linear equation. Thus the results are significant and the proposed hypothesis is accepted. And the coefficient of determination which shows the magnitude of the influence of the group investigative learning model on students' interest in learning is r2 = 0.6227 or 62.27%, it can be said that the group investigation model has a significant effect on students' interest in learning.